Quality of Life among Substance Use Disorder Patients in Khyber Pakhtunkhwa, Pakistan - Bakht Zada, Muttahid Shah, Aimen Saleem, Rabbia Ashraf, Asma Hameed, Aasma Yousaf (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: This study aimed to evaluate the quality of life (QoL) of substance use disorder (SUD) patients in Khyber Pakhtunkhwa, Pakistan. Design: A cross-sectional study Setting and Participants: 500 substance use disorder patients were selected from the seven drugs rehabilitation centers of Khyber Pakhtunkhwa, Pakistan. Methods: This study was carried in seven drugs rehabilitation centers of Khyber Pakhtunkhwa, Pakistan between August 08, 2019, and December 2020. A cross-sectional study design was used to assess the QoL among 500 substance use disorder adult patients who were taking initial rehabilitation treatment via a convenient sampling technique. The WHOQOL-BREF Field Trial Version was used to measure the QoL. Results: This study found that more than 75% (very poor: 27.8%, poor: 49.8%) substance use disorder patients had a poor perception of the QoL, 81% (very dissatisfied: 33.8%, dissatisfied: 47.2%) patients were dissatisfied with the overall perception of the health. The four domains of QoL of SUDs patients were also disturbed. Conclusion: The current finding of this study illustrated that people with SUDs need more attention for their QoL and well-being.